Reviewing scientific works in psychology - Sternberg, Robert J. (American Psychological Association, 2006)
(from the preface) The motivation for this book was the realization that although many academics and others are called on to do reviewing, very few of them have any formal training, or sometimes, informal training, in how to referee. We who write all know how disconcerting it is to get a review that is either mindless or worse, savage. The goal of this book is to teach anyone who does reviewing the basic skills needed to be a competent reviewer. These skills include competence in evaluating psychological work and competence in communicating that evaluation. The chapters cover a wide variety of review types, ranging from reviewing articles to reviewing grant proposals to reviewing book proposals. This book is for anyone who needs to review and who wants to ensure that he or she writes the same kind of review he or she would hope to receive.